Management Of a 56 Year-Old Female Patient with Herpes Zoster Through a Family Medicine Approach in Panjang Primary Healthcare Center - Itsa, Nando Abdila; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2025)
Herpes zoster is a disease caused by reactivation of the Varicella Zoster Virus which remains latent. The incidence of shingles increases with age and the immune system weakens. Herpes zoster is a disease that can recur at any time, so it needs to be treated holistically. The purpose of this case report is to implement a holistic and comprehensive family doctor service by identifying risk factors, clinical problems, and patient management based on evidence-based medicine which are patient centred, family approach, and community oriented. This study is a case report study. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family), physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment was based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Patient Mrs. S, 56 year-old, complaints of small nodules in groups containing fluid accompanied by sensations of pain, heat and itchy on the right side of his back since 8 days ago. The complaint began with fever a day before. The patient has a previous history of chickenpox. Non-medical and medical interventions are performed on patients and their families. The result reveals that the patient can follow these recommendations. Management has been given according to management guidelines. Good progress has been seen in patients starting from a decrease in clinical symptoms to changes in behavior. The role and support of the family is needed in the care and treatment of patients.